2012
DOI: 10.1371/journal.pone.0046692
|View full text |Cite
|
Sign up to set email alerts
|

A Brain-Computer Interface Based Attention Training Program for Treating Attention Deficit Hyperactivity Disorder

Abstract: Attention deficit hyperactivity disorder (ADHD) symptoms can be difficult to treat. We previously reported that a 20-session brain-computer interface (BCI) attention training programme improved ADHD symptoms. Here, we investigated a new more intensive BCI-based attention training game system on 20 unmedicated ADHD children (16 males, 4 females) with significant inattentive symptoms (combined and inattentive ADHD subtypes). This new system monitored attention through a head band with dry EEG sensors, which was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
186
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(196 citation statements)
references
References 31 publications
0
186
0
10
Order By: Relevance
“…Reason for exclusion Barnett et al [86] Participants are teachers Benyakorn et al [87] Not interventional Bishop [88] Intervention not technology Bonarini et al [89] Population focus not ADHD Bul et al [90] Outcome measures do not assess ADHD-related difficulties Chan et al [91] Not interventional Chen et al [92] Not interventional Christiansen et al [93] Intervention reliant on others Dale and Grut [94] Not exclusively for ADHD Duffy [95] Population focus not ADHD Enebrink et al [96] Population focus not ADHD References Reason for exclusion Epstein et al [97] Intervention reliant on health care professionals Fiellin et al [98] Population focus not ADHD Frutos-Pascual et al [99] Population focus not ADHD Frutos-Pascual and GarciaZapirain [100] Participants typically developing, not ADHD Gray et al [72] ADHD not primary diagnosis of participants Halperin et al [101] Intervention not technology Janeslätt et al [102] Intervention not technology Kim et al [103] Intervention not technology Lim et al [104] Intervention reliant on health care professionals Mazurek and Engelhardt [105] Not interventional Myers et al [106] Participants ADHD diagnosis not confirmed Nie et al [107] Intervention not technology Pandria et al [108] Not interventional Rohani et al [109] Participants ADHD diagnosis not confirmed Rosch and Mostofsky [110] Not interventional Schafer et al [111] Participants not received ADHD diagnosis Schuck et al [112] Participants not received ADHD diagnosis Shah et al 2012 Not interventional Silva et al [113] Technology as outcome measure, not intervention Steeger et al 2016 Participants ADHD diagnosis not confirmed Stephenson [114] Population focus not ADHD Tse et al …”
Section: Appendix 2: References and Reasons For Exclusionmentioning
confidence: 99%
“…Reason for exclusion Barnett et al [86] Participants are teachers Benyakorn et al [87] Not interventional Bishop [88] Intervention not technology Bonarini et al [89] Population focus not ADHD Bul et al [90] Outcome measures do not assess ADHD-related difficulties Chan et al [91] Not interventional Chen et al [92] Not interventional Christiansen et al [93] Intervention reliant on others Dale and Grut [94] Not exclusively for ADHD Duffy [95] Population focus not ADHD Enebrink et al [96] Population focus not ADHD References Reason for exclusion Epstein et al [97] Intervention reliant on health care professionals Fiellin et al [98] Population focus not ADHD Frutos-Pascual et al [99] Population focus not ADHD Frutos-Pascual and GarciaZapirain [100] Participants typically developing, not ADHD Gray et al [72] ADHD not primary diagnosis of participants Halperin et al [101] Intervention not technology Janeslätt et al [102] Intervention not technology Kim et al [103] Intervention not technology Lim et al [104] Intervention reliant on health care professionals Mazurek and Engelhardt [105] Not interventional Myers et al [106] Participants ADHD diagnosis not confirmed Nie et al [107] Intervention not technology Pandria et al [108] Not interventional Rohani et al [109] Participants ADHD diagnosis not confirmed Rosch and Mostofsky [110] Not interventional Schafer et al [111] Participants not received ADHD diagnosis Schuck et al [112] Participants not received ADHD diagnosis Shah et al 2012 Not interventional Silva et al [113] Technology as outcome measure, not intervention Steeger et al 2016 Participants ADHD diagnosis not confirmed Stephenson [114] Population focus not ADHD Tse et al …”
Section: Appendix 2: References and Reasons For Exclusionmentioning
confidence: 99%
“…Task focus  Abilities of game players (action video games, puzzle games) [4,[10][11][12][13] Education/Training/Health Awareness focus  Cyber-therapy classroom [14]  Intelligences [15]  Health awareness [16,17]  Cognitive (working memory) training [18] Medical/clinical focus  CBT (cognitive behavioural therapy) [19]  Cognitive tests: CPT (continuous performance test) [7,20,21]; Stop-signal or Go/No-go [22,23]  Working memory [24][25][26][27]  Eye-gaze [28][29][30]  Neurofeedback/Brain Computer Interfaces: EEG (electroencephalogram) theta/beta [31,32]; SCP (slow cortical potentials) [33,34]  Other biofeedback [9] It can be seen that most examples of games in the above list are concerned either with tasks to assess the effect of game playing on human performance or are for therapy, and a number of these are based on cognitive tests used more generally. One CPT game devised by the authors and other colleagues, SnappyApp, was intended for monitoring only [21] (see later), while another, QbTest, has been developed to aid diagnosis and monitoring [7].…”
Section: B Evidencementioning
confidence: 99%
“…Another involved a pole-vaulting mouse, the player being required to change the colour of the pole according to the SCP amplitude in relation to its baseline, to enable the mouse to jump [34]. An alternative neurofeedback approach reported recently (in the Cogo Land game) is to identify individualised EEG features reflecting attention and train the ability to modulate this parameter [32].…”
Section: Educational or Medical/clinical Focusmentioning
confidence: 99%
“…Contemporary outcomes from the use of BCI-based games (e.g. MindBall), BCIs in ADHD treatment [10], and biofeedback may be useful, but we do not know if previous experiences in this area may be generalized. Contemporary neurofeedback aims at:…”
Section: Researchmentioning
confidence: 99%